Heat shock alters pea aphid–Buchnera interactions: negative allometry of gene densities. Issue 5 (12th March 2021) - Parven, Nousheen; Yao, Izumi; Kanbe, Takashi; Akimoto, Shin‐ichi
Abstract: In the face of global climate change, the understanding of how aphid‐symbiont relationships are affected by heat shock is critical. We evaluated the effects of heat shock on the pea aphid, Acyrthosiphon pisum Harris (Hemiptera: Aphididae), and its obligate endosymbiont Buchnera aphidicola Munson et al. by means of quantitative PCR in treated aphids and their offspring. First‐instar aphids received a single heat shock (35 °C for 6 h), repetitive heat shocks (repeat of the single heat shock for 3 days), or a control treatment (constant 20 °C). We evaluated the impacts on aphid body length and Buchnera and aphid gene densities, estimated from the number of copies of bacterial 16S‐rRNA and nuclear elongation factor 1‐alpha (EF1α) genes, respectively. Heat shock negatively affected aphid body length and Buchnera and EF1α gene densities. Heat‐shocked aphids contained lower densities of Buchnera and EF1α genes than control aphids when body length was kept constant. When Buchnera and EF1α gene densities were represented on a log–log scale, Buchnera densities increased with EF1α densities in all treatments, but Buchnera densities showed negative allometry with EF1α densities. Compared to control aphids, heat‐shocked aphids contained lower Buchnera densities relative to EF1α densities. Some heat‐shocked aphids became sterile if their Buchnera gene density was lower than a threshold (ca. 42 000 copies). The offspring of aphids subjected to a single heat shock recovered the number of Buchnera, but the offspring of aphids subjected to repetitive heat shocks exhibited markedly lower Buchnera and EF1α densities. Thus, heat shock negatively affects both aphid and Buchnera cell proliferation, in the heat shock‐treated generation as well as in their offspring, but the impact is more severe on Buchnera . Because the symbiont supplies essential amino acids, vitamins, and an essential protein, this could reduce aphid development and reproduction and possibly leads to extinction of local populations. Abstract : Because of global climate change, a profound understanding of how aphid‐symbiont relationships are affected by heat shock is critical. We showed that heat shock negatively affects both pea aphid, Acyrthosiphon pisum (Hemiptera: Aphididae), and symbiont ( Buchnera aphidicola ) cell proliferation, in the heat shock‐treated aphids as well as in their offspring. The impact is more severe on Buchnera . Because the symbiont provides an essential protein, this could reduce aphid growth and development and possibly leads to local population extinction.